Sustainable Brand Trust in Mobile Banking: A Case Study of BSI Mobile User Reviews on Google Play - Tiandini, Novian; Hidayatullah, Haqqi (UI Scholars Hub, 2025)
In contemporary times, communication is important in resolving problems or crises in various field. One of them in digital transactions. The digital transactions are a frequently performed activity, including the use of mobile banking (m-banking), which has become an essential application due to the high volume of transactions utilizing it. Bank Syariah Indonesia (BSI) mobile is one of Indonesia's mobile banking services that experienced disruptions for several days in May 2023. Even BSI issued an official statement regarding the issue through their social media. This has the potential to affect users' trust in their brand, while a brand's strength is built over a long and continuous period with efforts to maximize value and assets becoming the roots of the brand itself. The purpose of this research is to analyze how BSI Mobile user reviews on Google Play Store in 2023 impact brand trust. This qualitative research employs a case study approach. Data was collected using text mining as the primary source, interviews as the secondary, and literature review. A review of BSI Mobile on the Google Play Store indicated that overall, users' trust in BSI Mobile in 2023 was relatively positive. BSI responded to user reviews on the platform to effectively communicate during a crisis and succeeded in building sustainable brand trust with their users.